Cilioretinal Artery Occlusion - Stoffelns, B. M.; Laspas, P. (Klinische Monatsblätter für Augenheilkunde, 2015)
Background: The aim of this study was to evaluate characteristic findings and functional outcome of this rare type of retinal vascular occlusion in a large patient series. Patients and Methods: A retrospective chart review of all patients with a cilioretinal artery obstruction (CAO) seen at the University Eye Clinic Mainz (Germany) over a ten-year period between 1/1999 and 12/2008 was undertaken. The mean follow-up amounted to 42 months. Results: Thirty-three eyes were diagnosed with CAO. Three distinct groups were differentiated: (i) isolated CAO in 20/33 eyes; visual outcome achieving 20/50 in 17/20 eyes; (ii) CAO combined with central retinal vein occlusion in 9/33 eyes; visual outcome achieving 20/50 in 5/9 eyes; (iii) CAO combined with anterior ischaemic optic neuropathy in 4/33 eyes; associated with giant cell arteriitis in 4/4 eyes; visual outcome achieving 20/160 in 1/4 eyes. Conclusions: The visual prognosis of CAO is significantly better than for other types of retinal artery occlusions, with the exception of cases associated with giant cell arteriitis.
Keywords: zilioretinale Arterien; retinaler Gefäßverschluss; zilioretinaler Gefäßverschluss; Riesenzellarteriitis; retinaler Zentralvenenverschluss